Financial Cycles and Fiscal Multipliers - Sebastian Gechert; Rafael Mentges (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2017)
We show that fiscal multiplier estimations may be biased by movements in asset and credit markets, as they facilitate spurious correlations of changes in cyclically adjusted revenues and spending with GDP growth via an identification bias and an omitted variable bias, thus overstating episodes of expansionary consolidations and downplaying contractionary consolidations. When controlling for asset and credit market movements in otherwise standard approaches to identification, we find multipliers to increase on average by 0.3 to 1 units. Fiscal consolidations are thus more likely to be contractionary and more harmful to growth than expected by some strands of the existing literature.
Keywords: C22; E62; H30; 330; multiplier effects; fiscal policy; asset markets; credit markets